(untitled) (American Journal of Business Management, Economics and Banking, 2023)
This study aimed to investigate the impact of financial technology dimensions on improving the quality of electronic banking services at Jordanian commercial banks in the capital, Amman, from the viewpoint of bank customers. Where the comparison method was adopted for previous studies. The study concluded that there is an effect of electronic financing, electronic lending, and automatic teller machines in improving the quality of electronic services in Jordanian commercial banks in the capital, Amman. Accordingly, the study recommends the need for Jordanian commercial bank administrations in the capital, Amman, to pay attention to developing electronic payment services and deepening customers’ understanding of electronic payment services so that they can benefit from them more, in addition to educating customers about the importance of using electronic banking services, and the inclusion of all possible services in electronic services.